Pengaruh Struktur Kepemilikan Saham, Struktur Modal, Dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2015 - 2020 - Wari, Mega Ardianis; Trisnaningsih, Sri (Universitas Pendidikan Ganesha, 2021)
The value of the company is the result of the company's performance and reflects the share priceeformed by supply and demand in the stock market. The aim is to analyze and examine the effect of share ownership structure proxied by institutional ownership and managerial ownership, as well as capital structure proxied by DER, and profitability as proxied by ROE on firm value proxied by PBV in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) in 2015 -2020. Purposive sampling is used to determine sampling. The population of pharmaceutical companies is 10 companies. Samples according to the criteria are 30 samples from 5 companies for 6 years of observation. The analysis technique in this study uses multiple linear regression analysis. The data analysis test tool uses the help of the IBM SPSS version 26.0 application from windows. The results of this study indicate that institutional ownership has no significant effect on firm value, while managerial ownership has a negative and significant effect on firm value. At the same time, capital structure has a positive and significant effect on firm value, and profitability has a positive and significant effect on firm value.Â Â